An Assessment of City Council Performance in Improving Urban Management and Development Process from Citizen\'s Perspective: Case Study Tabriz Metropolitan - Abolfazl Ghanbari (تحقیقات کاربردی علوم جغرافیایی)
The Islamic City Councils as an important element of the urban management system as an institution, policymaker, decision maker, and legislator at the local level, have to be fully operational in order to fulfill their role of policymaking and oversight over all matters to be able to carry out policy and oversight tasks in all areas of the city and local organizations concerned. Therefore, the purpose of this study is to measure the effectiveness of city council performance in improving the process of sustainable urban management and development from the perspective of citizens in Tabriz metropolis. This study is practical in terms of purpose and descriptive-analytical in terms of nature and method and document studies and field surveys were used to collect data. The statistical population of the study is all citizens and residents over 18 years of Tabriz metropolis. According to the 2015 census, this city had a population of 1558693 people and 497898 households. Cochran formula was used to determine the number of samples from 327 subjects were selected. The data for the analysis of quantitative methods, descriptive and inferential statistics (one-sample t, Kruskal-Wallis ANOVA, regression and path analysis) were used. The results showed that the average index of the performance of Islamic councils is 2.76 and its T-statistic is -6.59, which shows the unfavorable performance of the city council and the performance of the Islamic Council of this city in district 9 (with an average of 248.80). district 8 (with an average of 239.38) and district 2 (with an average of 204.33) have been evaluated favorably compared to other regions. Also, the average of all indicators of empowerment of Islamic city councils in the field of empowerment of Islamic councils is lower than numerical utility 3 and their t-statistic is negatively estimated. Finally, the performance of the Islamic councils in the economic dimension (employment, income and investment) has had the greatest effect with an overall effect of 0.608 and the least effect in the physical dimension with an overall effect of 0.210 in the realization of sustainable development. Keywords: City Council Performance, Urban Management, Sustainable Urban Development, Tabriz Metropolis.